Urgency of equitable access to and quality of hemodialysis services at the community level - Wabula, La Rakhmat (Indonesian Journal of Health Services, 2025)
Chronic kidney disease (CKD) continues to increase in Indonesia and requires long-term kidney replacement therapy, particularly hemodialysis, to sustain patients’ lives. However, hemodialysis services remain largely centralized in urban hospitals, creating significant physical, financial, and psychological burdens for patients living in peri-urban and rural areas. Limited accessibility often reduces treatment adherence and negatively affects patients’ quality of life. This article highlights the urgency of expanding equitable access to hemodialysis services at the community level through the decentralization of dialysis units and the strengthening of community-based nursing roles. Community nurses play a critical role in patient education, self-management support, and continuity of care beyond the clinical setting. In addition, integrating psychosocial support, peer groups, and family involvement is essential to address the emotional challenges faced by hemodialysis patients. Strengthening community-level hemodialysis services is therefore a strategic approach to improve treatment accessibility, patient empowerment, and overall quality of life.